Design Implications from a Needs Assessment for AR-Based Digital Learning Materials with Quizizz Integration in Secondary Education - Lilis Marina; A Arcat; S Sohibun; Aay Susilawati; Muchamad Subali Noto; Astri Wahyuni; Dianne Amor Kusuma (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2026)
In the context of global secondary education, rapid technological advancements have revolutionized learning environments. Educators are increasingly integrating immersive and interactive tools to better engage digital-native students. Augmented Reality (AR), when combined with gamified learning platforms, has shown great potential to boost student participation and comprehension. This study aims to analyze and compare the learning needs of Madrasah Tsanawiyah (MTs), including Islamic boarding schools, and Junior High School (JHS) students regarding AR-based digital learning materials integrated with the Quizizz platform. Using a descriptive quantitative design, the study employed data triangulation through questionnaires, classroom observations, and interviews to obtain a comprehensive view of students’ needs and preferences. The results indicate that both MTs and JHS students share similar needs for AR-based learning materials, particularly in interactive visualization, immediate feedback, and gamification features, although differences were found in specific interaction and feedback preferences. In conclusion, integrating AR technology with Quizizz can create more engaging and adaptive learning environments for secondary students. The study implies that Islamic education institutions can effectively adopt AR-based digital learning to support active learning, strengthen student engagement, and align instructional practices with contemporary technological developments.